Implementation of e-Government through System Village Information (SID) (Case Study of Talaga Jaya Village, Garut Regency) - Adnan, Iis Zilfah; Adnan , Zulkifli; Fadhlurrohman, Mochammad Iqbal; Fauzan, Hasbi Shiddiq (Sinergi International Journal of Communication Sciences, 2024)
This study is to study the implementation of System Village Information (SID) in Talaga Jaya Village, Garut Regency, as part of e-government development to increase service to the public and participation of the community. Implementation model approach Edward III's policies were used to analyze four main dimensions: communication, resources power, disposition, and structure bureaucracy. The result shows that the constraint mainly lies in its limitations in infrastructure technology, low digital literacy of society, and lack of capacity to source power for humans at the village level. Thus, SID began to impact positive open access information and encouraged the involvement of the public in the process of governance of the village. Research This recommends improving training for the device village, strengthening infrastructure technology, and intensive socialization to push the community to adopt SID. Further implementation Good expected can create a governance​ government transparent, efficient, and responsive village. This article becomes an essential guide for other villages that want to utilize digital technology to serve the public.